Subjective responses and cardiovascular effects of self-administered cocaine in cocaine-abusing men and women - Lynch, Wendy J. (2008)
This study aimed to examine sex differences in cocaine self-administration and cocaine-induced subjective and cardiovascular measures. The research was based on secondary analysis of data collected in our human laboratory in which subjects self-administered cocaine infusions (8, 16 and 32 mg/70 kg) over a 2-hour period under a fixed ratio 1, 5 minute time out schedule in three test sessions. Subjects were 10 women and 21 men with a history of either cocaine abuse or dependence who were not currently seeking treatment. Women and men self-administered similar amounts of cocaine. None of the subjective effects measures showed a significant main effect of sex during the cocaine self-administration session. Significant interactions were observed for subjective ratings of ‘high’ (sex × time) and ‘stimulated’ (sex × time × dose), with women reporting lower ratings over time/doses than men. Relative to men, cocaine produced dose- and time-dependent increases in feelings of hunger (i.e., reduced appetite suppression) in women. Systolic and diastolic blood pressures showed different patterns of change in men and women, with women showing less robust cocaine-induced increases than men. Taken together, these findings suggest that women and men may differ in their subjective and cardiovascular responses to self-administered cocaine. Further research that prospectively controls for hormonal influences upon these measures is needed.